What’s the issue with proportionality in the Danish parliamentary election law – and how should it be addressed? - Elklit, Jørgen; Holdum, Sebastian Tim; Klausen, Frederik Ravn (Politica, 2025)
The 2022 parliamentary elections in Denmark secured 50 seats for the Social Democrats, one more than would have resulted from a proportional seat allocation based exclusively on the parties’ share of the votes. This was unexpected as the seat allocation system (Hare-LR) had, for a long series of elections, ensured that parliamentary seat allocations in Denmark usually stayed within the quota (cf. Balinski and Young (2001/2010). One cannot determine whether this was a so-called 100-year event or simply a foreseeable consequence of the changing relative sizes of the parties. In addition to this uncertainty, we note that the current parliamentary electoral law does not contain explicit rules for how to address more complex seat allocation situations than what surfaced in 2022. We, therefore, suggest that the relevant section of the law be revised as a matter of urgency. We identify two possible ways of doing this. One means that the proportionality principle might still be compromised; one will put an end to the current finality of allocation of the 135 MMC seats. The choice between the two solutions is obviously of a political nature. We suggest that the issue be addressed in parliament as a matter of urgency as no one can tell when the seat allocation in parliament might be more complicated and more politically sensitive than in 2022.